Keanekaragaman Artropoda Predator pada Tanaman Kentang (Solanum tuberosum L.) yang Diaplikasikan Pestisida Nabati Batang Tembakau dan Mimba - Rizky, M. Muslihan; Sarjan, Muhammad; Stella Petrunella Thei, Ruth (Journal of Microbiology, Biotechnology and Conservation, 2025)
This study aims to determine the diversity, evenness, dominance and abundance of predatory arthropods in potato plants that have been applied with plant pesticides from tobacco stems and neem. This research was conducted in June-August 2022 on land owned by farmers in the Sembalun Bumbung area, Sembalun District. This study used an experimental method with field and laboratory experiments. The experimental design used in this study was RAK (Randomized Block Design) with 4 treatments (control, chemical pesticide abamectin, tobacco pesticide and neem pesticide) with 4 repetitions. Observations in the field were carried out 10 times with an interval of 1 time a week. The results of this study found 26 species of predatory arthropods belonging to 18 Families, 7 Orders and 2 Classes. The total number of individual predatory arthropods found was 662 individuals. The value of the diversity index (H') ranges from 1.59-1.88 which is classified as moderate. The value of the € evenness index ranges from 0.49-0.59 which is quite even. Dominance index values (D) ranged from 0.21-0.31 which indicated that no single species was too dominating. Abundance index (K) values ranged from 14,898-32,345 with the highest abundance in the neem plant pesticide treatment. The results of the ANOVA test analysis showed that all treatments had significant differences, so a BNJ (Honest Significant Difference) follow-up test was carried out with a level of 5%. Further test results showed no significant differences in diversity, evenness and dominance, but significantly different in abundance